Application of macro-bending for flat and broad gain EDFA - Hajireza, Parsin; Emami, Siamak Dawazdah; Abbasizargaleh, Soroush; Harun, Sulaiman Wadi; Kumar, Deepak; Abdul-Rashid, Hairul Azhar (Taylor & Francis, 2010)
Gain flattened C-band erbium-doped fiber amplifier (EDFA) is demonstrated using a macro-bending method. Various bending diameter and length of high concentration aluminosilicate EDFA are theoretically and experimentally analyzed. By varying the bending radius and the length of the doped fiber, the gain saturation effect as well as the energy transfer from shorter wavelength to a longer wavelength can be controlled to obtain a flattened and broadened gain profile in the C-band region. The amplifier uses a 9 m long erbium-doped fiber (EDF) with erbium ion density of 1.6 1025 ions m-3 and bending radius of 6.5 mm as a gain medium. The gain variation of the EDFA is obtained within 1 dB over 25 nm bandwidth of C-band region.